Functional outcomes in early (T1/T2) supraglottic cancer: a systematic review - Benjamin van der Woerd; Krupal B. Patel; Anthony C. Nichols; Kevin Fung; John Yoo; S. Danielle MacNeil (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Objectives Organ preserving surgery (OPS) and radiotherapy (RT) are both accepted treatment options for early stage supraglottic cancer (SGC). Radiation has supplanted surgery in most cases, because of the perception that surgery results in poorer functional outcomes. However, evidence suggests that OPS with a neck dissection may be associated with improved survival. Our objective was to conduct a systematic review of the literature to compare functional outcomes of OPS and RT for early SGC. Methods We searched Medline, EMBASE and Cochrane Central Register of Controlled Trials to identify studies. Studies were included if they reported functional outcomes on 10 or more patients with early stage SGC treated with radiation or OPS, including open partial laryngectomy, transoral laser microsurgery (TLM) or transoral robotic surgery (TORS). Two reviewers independently screened articles for relevance using pre-determined criteria. Results From 7720 references, we included 10 articles (n = 640 patients). 50% (n = 320) of patients were treated with surgery. Three head-to-head RT versus OPS papers were included, however different outcome measures were used for each group. Intractable aspiration management (including total laryngectomy or permanent tracheostomy) following OPS was reported in five papers representing 186 patients; the definitive intractable aspiration management rate was 2.6% (95% CI 1.0–6.8%). Four papers reported permanent G-tube rate for the surgical group (n = 198), calculating a rate of 5.3% (95% CI 2.6–10.5%), this was not reported for the RT group in any papers. One study reported quality of life. Two studies reported objective voice measures. Conclusions This systematic review revealed a paucity of objective measures and significant data heterogeneity, rendering the comparison of functional outcomes following OPS versus RT for early SGC limited. Future research should include objective measures of functional outcomes including laryngectomy rate, g-tube rate, tracheostomy dependence, quality of life, and voice quality measures.